Mohammad Ebrahim Jafari: Aesthetics of Painting in Poetry - A. V. Berezina (Концепт: философия, религия, культура, 2024)
The article is devoted to the creative heritage of the outstanding figure of Iranian culture — poet and artist Mohammad Ebrahim Jafari (1940–2018). The novelty of the presented research is determined by the almost complete absence of scientific works devoted to this issue: basic biographical facts, analysis of artistic language and the specific imagery of M. E. Jafari are poorly represented even in the Persian language. The purpose of the work is to identify the features of the national-cultural horizon of the synthetic genre combining painting and poetry developed by Jafari. To achieve this goal, it was necessary, firstly, to trace the poet’s biography; secondly, to clarify the nature of the artistic images created by him at different stages of his life and to analyze the original method of the author’s initiative as a way of artistic enrichment of the new synthetic genre. The multifaceted nature of the research subject determined the need for an interdisciplinary approach and the use of a complex of methods such as biographical, hermeneutic, and comparative typological. The author of the article has studied all the video materials and interviews of the poet published to date, his paintings, as well as a collection of selected poems. The author of the article also translated, for the first time, from Persian all the poetic material presented in the text. The study showed that M. E. Jafari, who does not differentiate the forms of creativity, easily transfers the stylistic techniques of his paintings to poems, which fills his lyrics with different shades of colors and smells. Poetic rhythm can be seen in his paintings, at the same time, abstract pictorial images embody the most significance for the poet in terms of acuity of perception, creating images of space and time as a unique experience, extremely concrete in its strength and depth. The masterly combination of abstract expressiveness and specificity of the sensual image makes it possible to attribute the deeply personal artistic creativity of M. E. Jafari to the cultural wave of new poetry, which meets the basic principles of the philosophy of Iranian modernism.